The effect of physical exercise and caloric restriction on the components of metabolic syndrome - Francisco Leonardo Torres-Leal; Mariana Dutilh de Capitani; Julio Tirapegui (Universidade de São Paulo, 2009)
Recent studies of the effects of physical exercise and caloric restriction have found several benefits on the metabolic and cardiovascular risk factors related to metabolic syndrome (MS). This review examines the current state of knowledge of the effects of physical exercise on the main pathologies associated with MS: obesity, insulin resistance, type 2 diabetes mellitus (DM2), dyslipidemias and hypertension. Although there are only a few randomized and controlled studies that evaluated the prevention and treatment of MS, strong evidence from controlled studies indicates that lifestyle changes that include regular physical exercise and caloric restriction are effective in preventing and treating DM2 in overweight individuals with reduced glucose tolerance. Likewise, epidemiologic studies suggest that regular physical exercise prevents the development of DM2 and cardiovascular disease. Based on current recommendations, it is important to increase the level of physical exercise at a moderate intensity to achieve good cardiorespiratory and muscular conditions and to promote fat mass reduction, with consequent reductions of risk of developing metabolic syndrome. Recentes estudos, relativos aos efeitos do exercício físico e da restrição energética, têm relatado diversos benefícios sobre fatores metabólicos e de risco cardiovascular relacionados à síndrome metabólica (SM). Esta revisão aborda os aspectos mais recentes dos efeitos do exercício físico sobre as principais patologias associadas à SM: obesidade, resistência à insulina, diabetes mellitus tipo 2 (DM2), dislipidemia e hipertensão. Embora estudos randomizados e controlados que avaliam a prevenção e o tratamento da SM sejam escassos, pesquisas controladas indicam fortes evidências de que mudanças no estilo de vida, incluindo a pratica de exercício físico regular e restrição energética, sejam eficazes na prevenção e tratamento de DM2 em indivíduos com sobrepeso e com tolerância à glicose diminuída. No mesmo sentido, estudos epidemiológicos sugerem que a prática regular de exercício físico previne DM2 e doenças cardiovasculares. Com base nas atuais recomendações, preconiza-se o aumento do volume total de exercício físico com intensidade moderada, na busca da boa condição cardiorrespiratória e muscular e da diminuição da massa gorda, com conseqüente aumento da proteção contra fatores associados ao desenvolvimento da síndrome metabólica.